A Comprehensive Study Of Miracle Tree, Shigru- A Review - chalmela, Neha; mishra, D Shiromani (International Research Journal of Ayurveda & Yoga, 2020)
Shigru (Moringa oleifera Lam.) is very common and well known herbal medicine. Generally Leaves,pods and flower of shigru are widely used in Indian kitchen as a vegetable due to it high nutritional values.properties of shigru extensively mentioned in various nighantus and samhitas owning to its broad therapeutic properties.the part of the subject which contain it is called samhita.studying the samhita makes sense of the subject. Shigru is widely described in both kaya chitiksa pradhan samhita and shalya chikitsa pradhan samhita. By the help of this review we can observe various uses and description of shigru in Several samhitas and nighantus which will be helpful for so many purpose.